Developing the Krajood Product Business Management of the 151st Infantry Regiment, Fourth Royal Thai Army Housewives Groups - Sriphong, Chompunuch; Arakkunakorn, Santi; Maneenin, Piyada; Kamphaengdee, Sasadee; Promvieng, Wallada (Area Based Development Research Journal, 2019)
The efficient business management affects the success of business operations. This research aims to develop the Krajood product business management of the 151st infantry regiment, fourth royal Thai army housewives’ group. The data was collected through group interviews, focus group discussions, and actual involvement in developing the business management of this group with the focus on the participation of group members throughout the entire process of development. They are involved in analyzing their business situation, defining guidelines for business management development and developing business management. The results reveal that this housewives’ group has changed in various aspects. 1) Group management aspect: the group has clear plans and management structure. Members of the group increase their business management capabilities and continuously operate their strong business. The group is legally registered for integration by community enterprise and an OTOP manufacturer and operator. Therefore, the government agencies support it by providing new machines, promoting a chance to join trade shows and enhancing the production knowledge of the members. 2) Finance and accounting aspect: the group has more income per month (25,000-30,000 baht) than previous months (10,000-12,000 baht). Besides, group members have correct knowledge and skills in accounting. 3) Production aspect: the group increases its production capacity due to more manpower and efficient machinery. Better productivity of the group members makes them receive community product standards for their products. 4) Marketing aspect: the group produces new products with added value, brand, product story, product detail, and product label. There are more distribution channels than before via fairs, online social media, and marketing mediators. Additionally, this group can establish the workplace to be a learning center for the community which strengthens the relationship and positive attitude of the people towards the military.